Abdominal skeletal muscle mass as a predictor of mortality in Japanese patients undergoing left ventricular assist device implantation. (30th March 2019) - Tsuji, Masaki; Amiya, Eisuke; Hatano, Masaru; Nitta, Daisuke; Maki, Hisataka; Bujo, Chie; Saito, Akihito; Hosoya, Yumiko; Minatsuki, Shun; Hara, Toru; Nemoto, Mariko; Kagami, Yukie; et al.
Abstract: Aims: We assessed preoperative muscle wasting in patients undergoing left ventricular assist device (LVAD) implantations using abdominal skeletal muscle images on computed tomography (CT) and explored the associations between the preoperative muscle wasting and clinical outcomes after LVAD implantation. Methods and results: We retrospectively examined the records of 111 patients who underwent continuous‐flow LVAD implantations as bridge‐to‐transplant therapy from January 2010 to December 2016 at our institution. After 33 patients were excluded, the study cohort consisted of 78 individuals. CT images used to calculate the skeletal muscle index (SMI) at the third lumbar vertebra level were obtained before the LVAD implantation procedures. Patients were classified as having muscle wasting if their SMI fell into the lowest gender‐based tertile. The median SMI for the study patients was 37.6 cm 2 /m 2 . The SMI cut‐off values for the lowest tertiles were 36.7 cm 2 /m 2 for men and 28.2 cm 2 /m 2 for women, resulting in 26 patients (33.3%) with muscle wasting in this study. During the mean follow‐up of 738 ± 379 days, there were 10 deaths (12.8% mortality). Seven of the 26 patients with muscle wasting (26.9%) died, and 3 of the 52 patients without muscle wasting (5.8%) died. The times to all‐cause mortality were significantly different between patients with and without muscle wasting ( P = 0.0094). Muscle wasting was found to be associated with mortality in univariate and multivariate Cox analyses (hazard ratio: 4.32; 95% CI: 1.19–20.2). Conclusions: Preoperative muscle wasting was associated with a higher mortality in patients with LVAD. Assessment of the abdominal skeletal muscle area on CT prior to LVAD implantation can help predict mortality.